Implementasi Metode Mimicry Memorization Pada Pembelajaran Bahasa Arab di Madrasah Tsanawiyah Pondok Pesantren Modern Al-Hasyimiyah Darul Ulum Sipaho - Siregar, Siti Marwiah; Akrim, Akrim (Fakultas Tarbiyah IAI Nasional Laa Rooiba, 2024)
This research aims to analyze the application of the Mimicry Memorization method in class VII students' Arabic language learning and what the advantages and disadvantages are of using the Mimicry Memorization method. This research was conducted at the Al-Hasyimiyah Darul Ulum Sipaho Modern Islamic Boarding School. This research uses a qualitative approach with descriptive research type. The data sources in this research are Arabic teachers and class VII students. Data collection techniques in this research include observation, interviews and documentation. Checking the validity of the data uses triangulation techniques. Data analysis techniques use data collection, data condensation, data presentation, and drawing conclusions. The results of the research in applying the Mimicry Memorization method in class VII Arabic language learning at the Darul Ulum Sipaho Islamic Boarding School through three stages, namely initial activities, core activities and final activities. The advantages of applying the Mimicry Memorization method are that it is fast and effective, a learning model, easier understanding, improving social skills, improving memory, and improving practical skills. The disadvantages of applying the Mimicry Memorization method are lack of in-depth understanding, limitations in speaking and writing, reliance on short-term memory, lack of development of critical thinking skills, difficulty adapting to new situations, and lack of interaction. With this research, it is hoped that students will be able to provide and be able to apply the Mimicry Memorization method to be more active and more effective in studying Arabic language subjects